Diversity of fatty acids in different coral species collected in the coastal sea of Nha Trang, Khanh Hoa - Dao, Thi Kim Dung; Dang, Thi Minh Tuyet; Nguyen, Thi Nga; Nguyen, Ba Kien; Trinh, Thi Thu Huong; Dang, Thi Phuong Ly (Vietnam Journal of Marine Science and Technology, 2024)
The total of 15 coral samples belonging to soft coral species Sinularia flexibilis, hard coral Acropora sp., and the hydrocoral Millepora platypylla, were collected in the coastal sea of Nha Trang, Khanh Hoa, Vietnam. In these samples, 39 fatty acids were identified in which Sinularia flexibilis sample identified 26 fatty acids, Acropora sp. identified 27 fatty acids, and Millepora platyphylla has the most diverse fatty acid composition with 35 fatty acids. In the coral samples of S. flexibilis, the difference between the ratio of total saturated fatty acids and the polyunsaturated fatty acids was much smaller than that of the other two species. The n-3/n-6 ratio is the highest among Millepora species, up to 4.45; in S. flexibilis and Acropora, this ratio can be lower than 1. Fatty acids 16:0 and 18:0 are the two main fatty acids in total; the content varies between samples of different species but is quite similar amongst samples of the same species. Fatty acids characterized by symbiotic microalgae 16:2n-7, 18:3n-6, 18:4n-3 Fatty acids 18:3n-6 were absent in S. flexibilis samples, minor content in M. platyphylla samples, and relatively significant in Acropora sp. (from 7.07% to 9.59% total fatty acids). Two fatty acids 16:2n-7 and 18:4n-3 were present in all 3 species, the highest in the sample S. flexibilis. The tetracosapolyenoic fatty acids 24:5n-6 and 24:6n-3 are soft coral marker fatty acids, present in only 5 samples of S. flexibilis with 24:5n-6 content ranging from 2.56% to 5.58% total fatty acids, 24:6n-3 is much lower (0.24% to 0.76%). The two PUFAs with the highest concentration were 20:4n-6 and 22:6n-3. 20:4n-6 was present in the total fatty acids of S. flexibilis with a quite high content (9.76% to 17.12% of the total axb), in contrast, the proportion was very low in five Millepora samples and five Acropora samples. 22:6n-3 was significantly high in the five Millepora samples (12.63% to 25.29% total fatty acids) and minor in the samples of the other two species.